Stefan Östersjö - Östersjö, Stefan (Sweden dB Productions, 1997)
ComposersCarter, Elliott (1908-2012)Dillon, James (b.1950)Donatoni, Franco (1927-2000)Lopez-Lopez, José Manuel (b.1956)Murail, Tristan (b.1947)Olofsson, Kent (b.1962)WorksCarter, E: ChangesDillon, J: Shrouded MirrorsDonatoni: Algo for guitarLopez-Lopez: Trio IIMurail: TellurOlofsson, K: The Garden of Earthly DelightsOlofsson, K: Treccia for guitarGroups & ArtistsArs Nova CopenhagenLabeldB Productions